Sounding together : collaborative perspectives on U.S. music in the 21st century - Garrett, Charles Hiroshi, 1966-; Oja, Carol J., 1953- (University of Michigan Press, 2021)
"Sounding Together: Collaborative Perspectives on U.S. Music in the Twenty-21st Century is a multi-authored, collaboratively conceived book of essays that tackles key challenges facing scholars studying music of the United States in the early twenty-first century. This book encourages scholars in music circles and beyond to explore the intersections between social responsibility, community engagement, and academic practices through the simple act of working together. The book's essays-written by a diverse and cross-generational group of scholars, performers, and practitioners-demonstrate how collaboration can harness complementary skills and nourish comparative boundary-crossing through interdisciplinary research. The chapters of the volume address issues of race, nationalism, mobility, cultural domination, and identity; as well as the crisis of the Trump era and the political power of music. Each contribution to the volume is written collaboratively by two scholars, bringing together contributors who represent a mix of career stages and positions. Through the practice of and reflection on collaboration, Sounding Together breaks out of long-established paradigms of solitude in humanities scholarship and works toward social justice in the study of music"--